Intercultural Bilingual Education for getting unity in diversity - Jaramillo García, Enrique M. (2017)
This article intends to be a contribution to a critical reflection about two educational divergent and conflicting models. On one side, there is the Intercultural Bilingual Education promoted by the Faculty of Education of the UNMSM and the Regional Association of Indigenous Peoples of the Central Forest and, on the other side, there is the official Western homogenizing reifying education, whose objective is to maintain social injustice and the status quo, promoted by the creole state. The idea is to train teachers of Intercultural Bilingual Primary Education loofing for getting unity among diversity, and tryingto rescue the historical memory and the valuable cultural capital of the indigenous peoples of the central region.